Abnormalities in Gut Microbiota and Metabolism in Patients With Chronic Spontaneous Urticaria - Wang, Xin; Yi, Wanyu; He, Liting; Luo, Shuaihantian; Wang, Jiaqi; Jiang, Li; Long, Hai; Zhao, Ming; Lu, Qianjin (Frontiers in Immunology, 2021)
Background: Increasing evidence suggests that gut microbiome play a role in the pathogenesis of allergy and autoimmunity. Association between abnormalities in gut microbiota and chronic spontaneous urticaria (CSU) remains largely undefined. Methods: Fecal samples were obtained from 39 patients with CSU and 40 healthy controls (HCs). 16S rRNA gene sequencing (39 patients with CSU and 40 HCs) and untargeted metabolomics (12 patients with CSU and 12 HCs) were performed to analyze the compositional and metabolic alterations of gut microbiome in patients with CSU and HCs. Results: The 16S rRNA gene sequencing results showed a significant difference in the β-diversity of gut microbiota, presented as the Jaccard distance, between patients with CSU and HCs. No significant differences were found in the α-diversity of gut microbiota between patients and HCs. At phylum level, the major bacteria in the gut microbiome of patients with CSU were Firmicutes, Bacteroidetes, Proteobacteria and Actinobacteria. At genus level, Lactobacillus, Turicibacter and Lachnobacterium were significantly increased and Phascolarctobacterium was decreased in patients with CSU. PICRUSt and correlation analysis indicated that Lactobacillus, Turicibacter, and Phascolarctobacterium, respectively, were positively related to G protein-coupled receptors. Metabolomic analysis showed that α-mangostin and glycyrrhizic acid were upregulated and 3-indolepropionic acid, xanthine and isobutyric acid were downregulated in patients with CSU. Correlation analysis between the intestinal microbiota and metabolites suggested that there was a positive correlation between Lachnobacterium and α-mangostin. Conclusions: This study suggests that disturbances in gut microbiome composition and metabolites and their crosstalk or interaction may participate in the pathogenesis of CSU.